Quality Development Management Of Educators In Improving Professional Competence (Descriptive Analytical Study At Smk Pelayaran Malahayati, Jakarta And SMK Pelayaran Buana Bahari Cirebon) - Bagaskoro; Iim Wasliman; Waska Warta; Agus Mulyanto (CV. AFDIFAL MAJU BERKAH, 2022)
This research is based on the reality of the low competence of educators or teachers who teach in shipping secondary schools, especially those with a background in maritime education. Various problems such as the lack of understanding of the concept of competency standards and basic competencies, the structure and mindset of Science, the use of technology in the learning process, as well as understanding related to the Standard of Training Certification and Watchkeeping for Seafarers (STCW 78) Amendment 2010 and the low ability to develop professionalism as educators. The purpose of the study was to analyze the management of educator development in improving professional competence. Specifically, it aims to describe the results of the analysis of planning, organizing, implementing, evaluating, supporting factors, obstacles, solutions and impacts in improving professional competence. This research uses qualitative approach with Case Study Method. Data collection techniques through interviews, observation and documentation studies. This research is based on the theory of quality while operational research is the theory of improvement (development) through teacher development. The results of this study are (1) planning carried out refers to the vision, mission and objectives. (2) the organization of coaching is highly dependent on school leaders and some policies are the authority of the foundation (3) the implementation of coaching is done by including in education/training, workshops, seminars, and skills training, attitudes and personality in accordance with the six values of life. (4) evaluation of coaching conducted by the institution internally. (5) supporting factors some teachers qualified academic S2, or qualified nautical expert/Teknika minimum level III, the availability of practical facilities in the form of simulators and workshops. (6) obstacles include not including coaching in the school's strategic plan, low interest in becoming educators, reluctance to attend training, (7) the impact of coaching is an increase in professional competence, pedagogic, social and personality in line with national standards of education and in line with the six values of life. (8) the solution of teaching transport beyond salary and honorarium, scholarship, discipline supervision of educators as a result of coaching there is an increase in the percentage of graduation of participants in the seafarers ' expertise exam which means that there is also an increase in the quality of graduates. Conclusion quality management development of educators managed to improve the professional competence of educators or teachers in SMK Pelayaran.